Effect Of Genetic And Non-Genetic Sources Of Variation On Service Period In Gir Cows - Kumar, Amit; Tomar, S.S.; Sharma, Harish; Rajoriya, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Effects of Inbreeding, sire, period and season of calving and parity on service period (SP) were studied on Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy Farm, Kasturbagram, Indore (M.P.). A total of 542 observations of SP on 191 cows were included in the study. The service period in these cows averaged 182.58±9.13 days and was significantly affected by inbreeding (p<0.01), parity (p<0.05) and season (P<0.05). The effects due to period and sire were non- significant. It was concluded that inbreeding had deteriorating effect on the service period and hence to reduce the service period in this herd inbreeding should be avoided by replacing the sires before their daughters attain sexual maturity.